Eradication of Tuberculosis– Current Status and the Way Forward (Medico Legal Update, 2020)
It is estimated that about 25% of humanity is infected with the bacterium Mycobacterium tuberculosis. Thatis about 2 billion people. Several new vaccines will pass Phase I clinical trials in the next few years. Thispaper briefly summarizes past and present challenges to developing a vaccine against tuberculosis as well astreating tuberculosis. TB is a pathogen that infects more individuals globally than any other communicabledisease. TB is particularly devastating in poor developing countries, notably in Africa and Southeast Asia.Despite the WHO’s efforts to overcome TB, Multi Drug Resistant (MDR) TB and Extremely Drug Resistant(XDR) TB are huge challenges.